Collaborative Efforts and Success Story of an Open‐Learning Program: Partnership Growth of the Research Data Management Librarian Academy (RDMLA). Issue 1 (13th October 2021) - Tang, Rong; Boyd, Ceilyn; Creamer, Andrew; Kriesberg, Adam; Martin, Elaine; Morin, Rebecca
Abstract: Launched in October 2019, the Research Data Management Librarian Academy (RDMLA) addresses the learning gaps in RDM training. Through a unique partnership among practicing librarians, LIS faculty, and industry, the RDMLA has produced a dynamic open learning experience, highlighting the benefits of collaboration and skill‐sharing. This collaboration's success lies in how the project leveraged each partner's strengths and experience while centering on the shared purpose, dedication to equitable learning, and mutual respect among the team members. This panel focuses on the collaborative efforts undertaken by the RDMLA leadership and instructors to develop an open‐access professional development education program. Five panelists will share their experience working on this large collaborative project from varying perspectives, the lessons learned while developing their content, the challenges they encountered, and their understanding of the benefits of such a collaborative endeavor in producing free, open‐access learning to foster a community of practice in RDM.